2020
DOI: 10.1002/kjm2.12210
|View full text |Cite
|
Sign up to set email alerts
|

miR‐495 targets ROCK1 to inhibit lipopolysaccharides‐induced WI‐38 cells apoptosis and inflammation

Abstract: Pneumonia is an inflammatory disease with leading mortality rate in children. It has been well established that microRNAs (miRNAs) have been regarded as critical regulator in acute lung injury. We intended to explore the effect and underlying mechanism of miR‐495 on lipopolysaccharides (LPS)‐induced WI‐38 cells. Here, we first found that miR‐495 was downregulated in serum of patients with acute stage pneumonia. To establish cell model of acute pneumonia, WI‐38 cells were treated with 20 μg/mL LPS, and qRT‐PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Extracellular vesicles carrying Caspase-3 in lung epithelial cells with hyperoxia treatment aggravated in ammatory lung responses via activating ROCK1 pathway [30]. Additionally, ROCK1 could regulate cell viability, apoptosis, and in ammation in ALI [16,[32][33][34]. Here, our results revealed miR-26a-5p directly combined with ROCK1 and suppressed ROCK1 expression.…”
Section: Discussionmentioning
confidence: 55%
“…Extracellular vesicles carrying Caspase-3 in lung epithelial cells with hyperoxia treatment aggravated in ammatory lung responses via activating ROCK1 pathway [30]. Additionally, ROCK1 could regulate cell viability, apoptosis, and in ammation in ALI [16,[32][33][34]. Here, our results revealed miR-26a-5p directly combined with ROCK1 and suppressed ROCK1 expression.…”
Section: Discussionmentioning
confidence: 55%
“…By using StarBase, the downstream genes of NEAT1 were screened, and the potential binding site between NEAT1 and miR-495 is presented in Figure 3a . Increasing evidence indicated that miR-495 acted as a vital regulator in the inflammation response of various diseases, such as pneumonia [ 22 ], inflammatory bowel disease [ 23 ], and ankylosing spondylitis [ 24 ]. Moreover, RT-qPCR analysis indicated that miR-495 expression was decreased in serum and middle ear effusion of OME ( Figure 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…37 Additionally, ROCK1 could regulate cell viability, apoptosis, and inflammation in ALI. 16,[38][39][40] Furthermore, Wang et al showed that ROCK1 could regulate cell pyroptosis to influence sepsis-induced acute kidney injury. 19 In our research, we determined that miR-26a-5p was directly combined with ROCK1 and suppressed ROCK1 expression.…”
Section: Discussionmentioning
confidence: 99%